Amplifying the spectrum of SPAST gene mutations - Verriello, Lorenzo; Lonigro, Incoronata Renata; Pessa, Maria Elena; Betto, Elena; Pauletto, Giada; Fogolari, Federico; Gigli, Gian Luigi; Curcio, Francesco (Acta Biomedica Atenei Parmensis, 2021)
Hereditary spastic paraplegias (HSPs) include a group of neurodegenerative disorders characterized by slowly progressive spasticity and weakness of the lower extremities, caused by axon degeneration of corticospinal tracts. Spastic paraplegia type 4 (SPG4) is the most common autosomal dominant form of HSP and is caused by mutations in the SPAST gene.SPAST gene encodes for the protein spastin, a member of the ATPases Associated with a variety of cellular Activity (AAA) family.We describe a newly variant in SPAST gene, within an Italian family affected by pure HSP. In particular, we found a heterozygous intragenic microdeletion of 3T in exon 13 of SPG4 gene. The 3T deletion results in a mutated protein with a unique leucine residues deletion at the protein position 508, in the AAA ATPase domain. This variant is not registered in any public database either as rare normal variant nor as mutation in SPAST gene and the importance of this aminoacid is confirmed by the absolute conservation in multiple alignments with diverse species. We conclude that the novel SPAST gene variant identified is probably pathogenic and destabilizes the precise arrangement of the nucleotide binding domain, with a consequent loss-of-function of the mutated spastin protein.